A snapshot of young children’s mathematical competencies: Results from the Longitudinal Study of Australian Children - MacDonald, Amy; MacDonald, A; Carmichael, Colin (My University, 2016)
This article presents a snapshot of the mathematical competencies of children aged four to five years in Australian early childhood education settings, as perceived by their educators. Data are presented from a nationally-representative sample of 6511 children participating in the Longitudinal Study of Australian Children (LSAC). The results reveal that children are seen to possess a number of mathematical competencies at 4-5 years, with the majority of children displaying interest in mathematics. Moreover, differences were noted with respect to the different program types in which the children participated. These results are discussed in relation to previous research, and implications for future research, policy and practice are presented.
Keywords: Education and Training -- Early Childhood; Education and Training -- Literacy and numeracy; Learning, education and training; Education and Training; Early Childhood; Literacy and numeracy; Learning, education and training